Game Theory for Computer Games Design. Issue 7 (November 2019) - Taylor, Mark; Baskett, Mike; Reilly, Denis; Ravindran, Somasundaram
Designing and developing computer games can be a complex activity that may involve professionals from a variety of disciplines. In this article, we examine the use of game theory for supporting the design of gameplay within the different sections of a computer game and demonstrate its application in practice via adapted high-level decision trees for modeling the flow in gameplay and payoff matrices for modeling skill or challenge levels.